The Pedagogical Perspective on Using Systemic Functional Linguistics (SFL) and Multimodality in EFL Classroom. - Faisal, Wafaa Mokhlos; Al Jebouri, Riyadh Sarhan Jabur (Tasnim International Journal for Human, Social and Legal Sciences, 2024)
This study aims to investigate the application of the Systemic Functional Linguistics (SFL) approach and Multimodality in genre-based learning, with a particular emphasis on textual metafunction. The research examined the coherence and cohesion of student learning patterns. Iraqi EFL teachers utilized basic frequency observation to support the use of Multimodality genre. The study point out that the texts exhibited certain aspects of coherence and cohesion and a limited understanding of the instructional genre, which is dependable with the findings of universal and regional studies. In some instances, however, textual metafunction in educational learning was either inappropriate or lacked target language complexity. The learners occasionally demonstrated a need for certain genre-specific elements, excessive reliance on simple, cohesion-promoting devices, and limited use of more complex devices. This paper aims to examine the implications SFL and multimodality to help students produce more proficient and persuasive communication context.